A cross-sectional study to assess acute malnutrition among under-5 children in the field practise area of a teaching hospital in Chennai - Naresh, Sulekha (J Family Med Prim Care, 2021)
CONTEXT: Malnutrition is one of the leading problem mainly in childhood, affecting growth and development especially under 5 years of age. According to NFHS-4, under-5 children about 27% are stunted, 20% are wasted and 24% are underweight. Determining acute malnutrition (wasting) and its factors is necessary to prevent complications. AIMS: To assess acute malnutrition among under 5 years children and determine associated factors responsible. SETTINGS AND DESIGN: Cross-sectional study done at field practice area under a teaching hospital in Chennai. MATERIALS AND METHODS: Totally, 149 children under 5 years of age were selected and assessed for acute malnutrition using WHO standards (Z-scoring) by calculating weight for height. Questionnaire for checking associated factors was used. STATISTICAL ANALYSIS USED: Data were entered in excel spreadsheet and analyzed using SPSS software version 16 and for inferential statistical analysis was done using Chi square test. RESULT: Among the study population, 87.2% children were normal, 10% of children had wasting (below -2 S.D.) and 2.8% of children had severe wasting (below -3 S.D.). Wasting was also prevalent among people of low socioeconomic class and was maximum in children of age group 1-3 years. Low birth weight, absence of exclusive breast feeding and complementary feeding practices, partial immunization and other illnesses also had effect, leading to acute malnutrition. CONCLUSION: Level of acute malnutrition in the field practice area is lesser than the national average and determines few factors associated with malnutrition among under – 5 children.